2023
DOI: 10.1021/acscatal.3c02303
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenolysis of Lignin Model Compounds on Ni Nanoparticles Surrounding the Oxygen Vacancy of CeO2

Abstract: The cleavage of C–O bonds presents the crucial step for realizing the depolymerization of lignin. Herein, we report that Ni nanoparticles (NiNPs) supported on CeO2 with oxygen vacancies (Ov) show high activity and selectivity in hydrogenolysis of C–O bonds of diphenyl ether (DPE, a lignin model compound), while single-site Ni (SSNi) is nearly inactive in the reaction. Temperature-programmed desorption (TPD) demonstrates that both DPE and H2 can be adsorbed and activated on NiNPs. Density functional theory (DFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 82 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…As displayed in Fig. 1l, in addition to peaks belonging to gaseous CO at 2117 cm −1 , 15,16 a new peak centered at 1847 cm −1 assigned to linear-type CO adsorbed on single Fe sites (even lower than that at 1888 cm −1 detected on the O v of CeO 2 ) 17 was detected and increased with CO pressure, indicating the existence of a certain number of Fe single sites. In our previous work, we reported that Fe atoms predominantly undergo substitutional doping into the CeO 2 lattice under the current calcination experimental conditions (900 °C and 6 h).…”
Section: Resultsmentioning
confidence: 88%
“…As displayed in Fig. 1l, in addition to peaks belonging to gaseous CO at 2117 cm −1 , 15,16 a new peak centered at 1847 cm −1 assigned to linear-type CO adsorbed on single Fe sites (even lower than that at 1888 cm −1 detected on the O v of CeO 2 ) 17 was detected and increased with CO pressure, indicating the existence of a certain number of Fe single sites. In our previous work, we reported that Fe atoms predominantly undergo substitutional doping into the CeO 2 lattice under the current calcination experimental conditions (900 °C and 6 h).…”
Section: Resultsmentioning
confidence: 88%
“…As a unique catalyst support material, cerium oxide (CeO 2 ) can maximize the activity of precious metals due to the existence of abundant oxygen vacancy defects. , At the same time, CeO 2 and precious metals can strongly interact, which limits the agglomeration of precious metals on the support. Thus, these metals can stably exist in a highly dispersed form, and lower precious metal loadings can be utilized. , Recently, Li and co-workers used CeO 2 -supported Ni nanoparticles to achieve the efficient catalytic hydrogen hydrolysis of diphenyl ethers . Datye and co-workers realized the oxidation of CO by loading single-atom Pt active sites on CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Li and co-workers reported that the higher activity for the hydrogenolysis of 2-phenoxy-1-phenethanol over carbon-supported Ni nanoparticles was ascribed to the lower H 2 dissociation energy and reduced energy barriers on Ni cluster compared with Ni single-atom in DFT simulations . Xie et al found that the adsorption of diphenyl ether on Ni 10 /CeO 2 (111) was stronger than that on the Ni SA /CeO 2 (111) by comparing the DFT-calculated energies and proposed the reaction mechanism for the DPE hydrogenolysis on Ni 10 /CeO 2 (111) . In these theoretical studies, there is a lack of electronic structure analyses that can be used to reveal the nature of the energy differences.…”
Section: Introductionmentioning
confidence: 99%